The Psychological Contract, Knowledge Management & Organisational Capacity - Blackman, Deborah; Phillips, Dianne (Journal of Knowledge Management Practice, 2009)
This paper considers the relationships between the psychological contract and the propensity to create, share and utilise organisational knowledge, thereby developing potential organisational capacity. It is widely accepted that organisational capacity will be affected by the way that knowledge is utilised within an organisation. It is argued that the way that individuals feel about their organisation must, inevitably, affect their willingness to engage with activities that lead to effective knowledge management and, consequently, the capacity of an organisation to improve and innovate will be determined by the psychological contract present within the organisation. Three case studies undertaken in the hospitality education industry are used to identify four key themes which affect the effectiveness of organisational knowledge management and are affected by the psychological contract: functionality, safety, opportunity and relationships. The final part of the paper begins to identify strategies that will support knowledge creation and absorption and, consequently, increase of organisational capacity within firms.